KEBIJAKAN REZIM OTORITER TERHADAP ISLAM POLITIK (STUDI KASUS REZIM SOEHARTO DAN ANWAR SADAT) - Mahmud Hamzawi Fahim Usman (CMES (Center of Middle Eastern Studies), 2013)
This dissertation titled "The Policies of Authoritarian Regimes towards PoliticalIslam: A Case Study on Soeharto’s and Anwar Sadat’s Regimes" attempts to answer thisquestion: what policies towards Political Islam were adopted by Soeharto’s and Sadat’sregimes and what are the similarities and differences between both of them as well astheir underlying factors? This dissertation is a library research with qualitative datausing descriptive, interpretative, and analytical approaches based on the theory of policy.  The policies of both regimes are classified into two broad strategies, namely: first,the subjugation of Political Islam’s power (through two modes: a. violence andmarginalization; and b. propaganda and image politics); second, the accommodation ofPolitical Islam (through two modes: social and religious appeasement; and legislativepolicy appeasement). Those policies are significantly of similar style and aim butdifferent in terms of order and tactic of implementation. In general, those policies areequally pragmatic and realistic for maximizing the regime’s strength and gains andoutrivaling all powers of Political Islam with view of achieving the state’s politicalstability and avoiding the emergence of legitimacy crisis owing to domestic situations.Therefore, the researcher refers to such policies as hegemonic regime’s domesticpolitical stability strategy.